Attention-deficit/hyperactivity disorder (ADHD) in adult obese patients referred to bariatric surgery. (1st June 2022) - Brancati, G.E.; Barbuti, M.; Weiss, F.; Calderone, A.; Santini, F.; Perugi, G.
Abstract : Introduction: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental condition characterized by symptoms of inattention, hyperactivity, and impulsivity, which only rarely remits in adulthood [1] . A positive association between ADHD and obesity has been repeatedly observed, especially in adult samples [2] . However, only a few studies investigated the prevalence and correlates of ADHD in obese patients seeking bariatric treatment [3, 4] . Objectives: Our study was aimed to examine the prevalence of probable ADHD comorbidity in a sample of obese patients referred for bariatric surgery. Secondly, we sought to characterize differences in eating behaviour between obese subjects with and without probable ADHD. Methods: The study sample was composed of 110 adult obese patients (BMI ≥ 30 kg/m2) consecutively referred for bariatric surgery to the Obesity Center of the Endocrinology Unit in Pisa University Hospital between November 2010 and May 2012. Probable ADHD was identified using a recently developed screening scale based on items selected from Symptom Check‐List‐90‐R (SCL-90-R) [5] . The extent of binge-eating/purging and night-eating behaviours were respectively estimated using the Bulimic Investigatory Test, Edinburgh (BITE) [6] and the Night-eating Questionnaire (NEQ) [7] . Wilcoxon test was used for statistical comparisons, with a significance level of p<0.05 set for all tests. Results: Probable ADHD was found in 14 subjects (12.7%, 95%CI=7.1-20.4%). Patients with probable ADHD showed significantly higher BITE symptom score (20.4±9.3 vs. 12.1±7.5, r=0.31, p=0.001) and NEQ total score (16.1±9.2 vs. 9.5±3.9, r=0.27, p=0.005). Conclusions: ADHD is a relatively common comorbidity in obese patients seeking bariatric treatment, which is positively associated with disordered eating habits, such as binge-eating/purging and night-eating behaviours. Disclosure: No significant relationships.